On the Assessment of the CO2 Mitigation Potential of Woody Biomass - Codina Gironès, Víctor; Peduzzi, Emanuela; Vuille, François; Maréchal, François (Frontiers in Energy Research, 2018)
Woody biomass, a renewable energy resource, accumulates solar energy in form of carbon hydrates produced from atmospheric CO2 and H2O. It is, therefore, a means of CO2 mitigation for society as long as the biogenic carbon released to the atmosphere when delivering its energy content by oxidation can be accumulated again during growth of new woody biomass. Even when considering the complete life cycle, usually, only a small amount of fossil CO2 is emitted. However, woody biomass availability is limited by land requirement and, therefore, it is important to maximize its CO2 mitigation potential in the energy system. In this study, we consider woody biomass not only as a source of renewable energy but also as a source of carbon for seasonal storage of solar electricity. A first analysis is carried out based on the mitigation effect of woody biomass usage pathways, which is the avoided fossil CO2 emissions obtained by using one unit of woody biomass to provide energy services, as alternative to fossil fuels. Results show that woody biomass usage pathways can achieve up to 9.55 times the mitigation effect obtained through combustion of woody biomass, which is taken as a reference. Applying energy system modeling and multi-objective optimization techniques, the role of woody biomass technological choices in the energy transition is then analyzed at a country scale. The analysis is applied to Switzerland, demonstrating that the use of woody biomass in gasification–methanation systems, coupled with electrolysers and combined with an intensive deployment of PV panels and efficient technologies, could reduce the natural gas imports to zero. Electrolysers are used to boost synthetic natural gas production by hydrogen injection into the methanation reaction. The hydrogen used is produced when there is excess of solar electricity. The efficient technologies, such as heat pumps and battery electric vehicles, allow increasing the overall efficiency of the energy system while generating demand for the solar electricity.